Antimicrobial activity of nigella sativa seed extract - Nor’ Aishah Hasan,; Mohd Zaini Nawahwi,; Haslinda Ab Malek, (Universiti Kebangsaan Malaysia, 2013)
Pathogenic bacterial infections have become a major health problem worldwide. New antimicrobial agents are urgently needed to overcome this problem. In this study, antibacterial activity of Nigella sativa seed extract against some pathogenic bacterial strains (Streptococcus pyogene, Pseudomonas aeruginosa, Klebseilla pneumoniae and Proteus vulgaris) was evaluated. Methanol extract at the concentration of 100 mg/mL had a remarkable sensitivity towards all tested bacteria in this study. Klebseila pneumonia and Proteus vulgaris showed resistance against aqueous extract at 20 mg/mL. Methanol extract of Nigella sativa exhibited significant antibacterial activity at the concentration of 50 mg/mL (p ≤ 0.01) against Streptococcus pyogenes with a greater inhibition zone of 19 mm, while a 15 mm zone of inhibition was observed in Pseudomonas aeruginosa, pneumonia and Proteus vulgaris. Kruskal Wallis analysis showed that both aqueous and methanol extract of black seed exhibited a greater inhibition on Gram positive bacteria (Streptococcus pyogenes) compared with Gram negative bacteria (Pseudomonas aeruginosa, Klebseilla pneumoniae and Proteus vulgaris). Our study also showed that species, strains and concentrations of Nigella sativa extract are some of the factors that may influence the sensitivity of the tested bacteria. A significant correlation was observed between zone of inhibition and concentration of extract.